Unique Physical Behavior with Two Main Integrated Types of Chemical Substances of Herbal Medicine based Insulin Leaf (Tithonia diversifolia (Hemsley) A. Gray (Asteraceae)): A Healthy Simple Natural Drink - Nur Arafah Mahubessy; Hanoch J. Sohilait; Hendry Izaac Elim (Faculty of Mathematics and Natural Sciences, University of Pattimura, 2021)
A healthy simple natural drink is introduced based on a deep physical research investigation into insulin leaf (Tithonia diversifolia (Hemsley) A. Gray (Asteraceae)). Such drink was simply fabricated using two steps process of heating and cooling, and then exposed according to 2 main unique physical properties of optical and electrical behaviors. It was well-known that Tithonia diversifolia (Hemsley) A. Gray (Asteraceae)) had been very attractive in the east Africa continent and in the most of areas in Asia continent, as well as in Indonesia country of over 14,480 islands as Daun Kembang bulan because of its various biological and chemical properties to sustain human being life on earth. In present paper, our findings are focused on the unique physical characters sustained with a simple theoretical model to explain the interplay quantity of mechanical vibration of 2 main compounds of Tagitinine A (C19H28O7) and Tagitinine C or artemisinic acid (C15H22O2) identified using HPLC in such natural healthy drink produced by our Herbal Blessing standard products in nanotechnology research center and innovative creation (PPNRI) at Pattimura university. Such interesting finding suggests that the interactive vibration only involved about 23.763 % mass of the total conserved mass